Identifying Leadership Skills Required in the Digital Age - Milan Frederik Klus; Julia Müller (Center for Economic Studies and ifo Institute (CESifo), 2020)
How should executives lead organisations and their employees in an increasingly digitalized business environment and what skills are needed to succeed? Although the evolution of digital technologies considerably changes working environments in organisations and creates new challenges for executives, only little research has been conducted on how these challenges and technology-driven changes are associated with requirements for the skill set needed by executives. In this paper, we bridge that gap by applying a three-stage research design. First, we develop a conceptual framework in which we categorise leadership skills included in the existing literature and associate them with tasks, management level, and leadership experience. To identify skills that are particularly relevant in the context of digitalisation, we conduct semi-structured interviews with executives and systematically investigate job advertisements for management positions. By triangulating the findings, we contribute new insights to the leadership literature and derive practical implications.
Keywords: M12; M15; M51; M54; O32; O33; 330; conceptual framework; digitalization; explorative study; leadership skills